If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + -4 + 6) = 5(x + -1 + 5) Reorder the terms: 6(-4 + 6 + x) = 5(x + -1 + 5) Combine like terms: -4 + 6 = 2 6(2 + x) = 5(x + -1 + 5) (2 * 6 + x * 6) = 5(x + -1 + 5) (12 + 6x) = 5(x + -1 + 5) Reorder the terms: 12 + 6x = 5(-1 + 5 + x) Combine like terms: -1 + 5 = 4 12 + 6x = 5(4 + x) 12 + 6x = (4 * 5 + x * 5) 12 + 6x = (20 + 5x) Solving 12 + 6x = 20 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 12 + 6x + -5x = 20 + 5x + -5x Combine like terms: 6x + -5x = 1x 12 + 1x = 20 + 5x + -5x Combine like terms: 5x + -5x = 0 12 + 1x = 20 + 0 12 + 1x = 20 Add '-12' to each side of the equation. 12 + -12 + 1x = 20 + -12 Combine like terms: 12 + -12 = 0 0 + 1x = 20 + -12 1x = 20 + -12 Combine like terms: 20 + -12 = 8 1x = 8 Divide each side by '1'. x = 8 Simplifying x = 8
| x/-8=-10 | | 5r/r-5-5r/r-6 | | Y=x/k/m | | F(5)=x^2-7 | | 7/8g=56 | | 2x^2+x-34=0 | | x^2+95=99 | | 5x-(4-2x)=7 | | x^2+19=119 | | 10x=x-3 | | x/(lnx)=4 | | (-1/2)^5 | | 14+3z-8-5z= | | x^2-25=144 | | 11y-14=7+14y | | 16x^2-25x=-9 | | 6x-6=3(x-2) | | 5w+10=2(4w+10) | | 1h+h=9 | | Y+3-28= | | w^2+12w-20=0 | | 3(x+2)=7(2x-1) | | 3w+10=3w+10 | | f(x)=3x^2+7x-5 | | 5y-19=12 | | 10x+9y=1200 | | 9p+7=6p+5 | | f(3)=3x^2-4x+5 | | 3ln(x+3)=-6 | | 2n-12=3n+9 | | (x+69)+2x=180 | | 10=5m(m-5) |